MILITARY CULTURE AND LEVELS OF MILITARY CULTURAL COMPETENCE - Siyovush Qaxxorov (Sciental Journals Publishing, 2025)
This article analyzes the content, significance, and stages of development of military culture competencies. It substantiates the crucial role of cultural, ethical, patriotic, and communicative competencies in professional training within the military sphere. These competencies contribute to the formation of professional knowledge, spiritual maturity, and social responsibility among youth.